313 A RETROSPECTIVE REVIEW OF THE PROGNOSIS AND RISK FACTORS ASSOCIATED WITH ENDOGENOUS ENDOPHTHALMITIS. (1st January 2006) - Lee, S. H.; Dovich, J.; Fan, J.
Abstract : Objective: To report the visual outcome, management, causative organisms, source of infection, and predisposing diseases in cases of endogenous endophthalmitis, which is defined as an intraocular infection resulting from a microorganism that has crossed the blood-ocular barrier initially focused at a distant infection site. Methods: This is a retrospective case series of 13 patients and 19 eyes that presented to the Loma Linda University Medical Center from January 1, 1987 to December 31, 2005. This study is ongoing. Results: All of the patients had a prior medical condition that predisposed them to this disease. These include diabetes, hypertension, heart disease, kidney disease, immune deficiency, and malignancy. Forty-six percent of the patients had bilateral endophthalmitis. The majority of cases were fungal (46%), while Staphylococcus aureaus accounted for 15% of the cases. Sources of infection were infected hospital tubing in 31% of cases, endocarditis in 15% of cases, and GI abscesses in 15% of cases. The majority of cases were managed with intravitreal antibiotics and vitrectomies with disappointing visual outcomes. Only three of the eyes had final visual acuities of 20/100 or better. Conclusion: These results represent a trend of increasing incidence of fungal endogenous endophthalmitis. They also indicate predisposing conditions and infection sources of this disease. Prognosis is poor in the majority of patients and is most likely determined by the extent of the infection and how soon the infection is treated.